2020
DOI: 10.2217/fon-2020-0443
|View full text |Cite
|
Sign up to set email alerts
|

Tivozanib, a highly potent and selective inhibitor of VEGF receptor tyrosine kinases, for the treatment of metastatic renal cell carcinoma

Abstract: The VHL mutation– HIF upregulation– VEGF transcription sequence is the principal pathway in the development of renal cell carcinoma. Tyrosine kinase inhibitors target the VEGF receptors to inhibit further growth of renal cell carcinoma tumors. Tivozanib, originally named AV-951 and KRN-951, is a novel, orally bioavailable VEGF tyrosine kinase inhibitor that is selective for VEGF receptors 1, 2 and 3. Further, only picomolar concentrations of tivozanib are required to target these VEGF receptors and prevent pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Tivozanib (Fotivda), formerly known as AV-951 or KRN-951, is an oral, potent, selective VEGFR TKI with a weak off-target effect [ 10 ]. The inhibitory effect on VEGFRs is stronger compared to other previously used TKIs in metastatic renal-cell carcinoma (mRCC) [ 11 ]. However, tivozanib can also inhibit c-kit, which is eight times less sensitive to tivozanib compared to VEGFR 1, 2, and 3.…”
Section: Reviewmentioning
confidence: 99%
“…Tivozanib (Fotivda), formerly known as AV-951 or KRN-951, is an oral, potent, selective VEGFR TKI with a weak off-target effect [ 10 ]. The inhibitory effect on VEGFRs is stronger compared to other previously used TKIs in metastatic renal-cell carcinoma (mRCC) [ 11 ]. However, tivozanib can also inhibit c-kit, which is eight times less sensitive to tivozanib compared to VEGFR 1, 2, and 3.…”
Section: Reviewmentioning
confidence: 99%
“…In the KEYNOTE 426 study, the pembrolizumab–axitinib combination showed superiority over sunitinib in terms of OS, PFS, and ORR [ 17 ]. However, the follow-up of the study data presented at the ASCO Annual Meeting 2020 showed a lack of maintenance in good-risk patients in terms of PFS and OS, with no significant differences between both combination and monotherapy after 23 months [ 31 ].…”
Section: Combination Therapy Versus Tki Alone In Selected Patient Subgroupsmentioning
confidence: 99%
“…Herein, enzalutamide is an anti-androgen that delays the progression of advanced prostate cancer for about 8 months, [90] whereas tivozanib is an anti-angiogenic agent blocking the tumor blood supply. [91] The main goal of this study is to determine whether the combination of these two drugs is more effective in delaying the progression of disease than using enzalutamide alone. The dose of the combination study is tivozanib daily oral for 21 days followed by 7 days break and enzalutamide daily oral for 28 days.…”
Section: Progress Of Clinical Investigations Of Anti-angiogenic Agents As Mono-or Combination Therapymentioning
confidence: 99%